Niektóre makroekonomiczne problemy sfery finansów w naszej gospodarce rynkowej - Łukawer, Edward (MITEL, 2004)
Przyczyny nierówności społeczno-gospodarczych w Polsce są poszukiwane zarówno w gospodarce realnej, jak i w sektorze finansowym. W niniejszym dokumencie szczegółowo omówiono niektóre aspekty tego ostatniego.

The reasons for socio-economic inequalities in Poland are sought both in real economy and in the financial sector. This paper looks in detail at some aspects of the latter.
Selected Macroeconomic Issues of the Financial Sector in Poland’s Market Economy